Continuous mining, its application in a metallic mining operation - Ortiz Sánchez, Oswaldo (2012)
The use of roadheader (RH ) equipment for the underground mining of zinc ores in the San Vicente reservoir is analyzed. The characteristics of the ore bodies of the deposit is described in terms of technical and economic terms for removal by continuous mining system . Compared with the method of room and pillar mining with filling up currently applied , through the present value (PV ) of the cost of the two mining systems determining the continuous mining method has the lowest present value cost . The alternative of continuous mining equipment with RH without the use of explosives to break the rock, compared to the current system of mined with explosives, has other advantages , such as reducing the rocky Massif instability caused by vibrations , surface generation uniform in the excavations , reducing environmental pollution by noise, dust and gases that produce the shots and diesel equipment inside the mine . The risk to personnel handling explosives and generated significant savings in maintenance costs and operation is avoided.